The Wounds and the Ascended Body: The Marks of Crucifixion in the Glorified Christ from Justin Martyr to John Calvin - Widdicombe, Peter (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2003)
AbstractThe question of whether the ascended and glorified body of Christ retains the marks of the wounds first became an issue of theological importance in the fifth century with the writings of Cyril of Alexandria and it continued to be developed until the Reformation, when both Luther and Calvin rejected the idea. For the patristic and medieval theologians, the enduring reality of the wounds testify to the intimate connnection between the economy of God’s salvific work within the created order and the eternal economy. It underscored God’s ongoing good intention for, and engagement with, fallen creation. However transformed in glory, the ascended Christ is not to be thought of as dehominised and the evidence of his history as the incarnate and suffering human being is not to be erased. Suffering and sinful humanity finds itself in the Son at the right hand of the Father and it can see there the evidence that the divine heart has and continues to beat with compassion for humanity in its continuing brokenness. It is the enduring presence of the marks of the wounds in heaven that testifies to the divine engagement with the sinful human condition, in both judgment and mercy, which in turn is the basis of humankind’s response of thankfulness.